Software design - David Budgen (Addison-Wesley, 1994)
The book surveys a wide range of forml and systematic methods, and examines their role in software engineering, comparing their strengths and limitations. It includes an analysis of the nature of the design process as applied to software, and of the consequences this has for design methods; an emphasis on design principles and strategies, including practical examples of different methods at work; an exploitation of strengths and weaknesses of a wide range of methods, for example, SSA/SD, JSP, JSD, Object-Oriented Design< SADT, SSADM and 'formal' methods including VDM